Regulation of transcription by factors interacting with the TATA binding protein - Yatherajam, Gayatri, author; Stargell, Laurie, advisor; Nyborg, Jennifer, committee member; Luger, Karolin, committee member; Laybourn, Paul, committee member; Suchman, Erica, committee member (Colorado State University. Libraries, 2004)
Transcription is an essential cellular process to maintain cell growth, differentiation and development. Most of these developmental processes require proteins and thus the process of decoding proteins from DNA (transcription) is a critical phenomenon. Several factors and multi-subunit complexes play essential functional roles in transcription. Among all these factors, the TATA binding protein (TBP) has a central and essential function. The binding of TBP to the TATA box of the DNA is the first and often the rate-limiting step of transcription initiation. There for this step is highly regulated. TFIID is a transcription factor that is constituted of TBP and 14 different TBP associated factors (TAFs). TAFs are known to have gene specific functions. In yeast, TFIID is approximately 1.2 MDa in size. To get a better understanding of the molecular organization of TFIID, we used a yeast two-hybrid approach to detail the TBP-TAF and TAF-TAF interactions. Every TAF exhibited a unique interaction profile. This study furthered our understanding of the organization of TFIID. Finally we delineate the TAF interaction regions within the scaffolding TAF, TAF1. TFIID interacts with TFIIA. However, the specifics of this interaction were not clear until we establish that TAF11 makes functional contacts between the rest of TFIID and TFIIA functioning as an essential link between these two transcription factors. Using point mutants of TAF11 and TFIIA, we show an in vivo compensatory interaction between these two factors thus establishing that TAF11 acts as a mediator between TFIID and TFIIA. MOT1 is a TAF known to have activation and repression function in transcription regulation. Not much is known about this intriguing protein and how it accomplishes this dual function. We tethered MOT1 to the DNA binding domain of a transcription factor and recruited it to the DNA to study its effects on transcription. Our findings clearly establish the repressive function of MOT1 in vivo. The studies presented here give us a better understanding of various facets of transcription regulation by factors that associate with TBP.
Keywords: biochemistry; molecular biology